Recent Multi-target Approaches on the Development of Anti- Alzheimer's Agents Integrating Metal Chelation Activity - Chaves, Sílvia; Várnagy, Katalin; Santos, M. Amélia (Current Medicinal Chemistry, 2021)
Alzheimer´s disease (AD) is the most common and severe age-dependent neurodegenerative disorder worldwide. Notwithstanding the large amount of research dedicated to both the elucidation of this pathology and the development of an effective drug, the multifaceted nature and complexity of the disease are certainly a rationale for the absence of cure so far. Currently available drugs are used, mainly to compensate the decline of the neurotransmitter acetylcholine by acetylcholinesterase (AChE) inhibition, though they only provide temporary symptomatic benefits and cannot stop AD progression. Although the multiple factors that contribute to trigger AD onset and progression are not yet fully understood, several pathological features and underneath pathways have been recognized to contribute to its pathology, such as metal dyshomeostasis, protein misfolding, oxidative stress and neurotransmitter deficiencies, some of them being interconnected. Thus, there is widespread recent interest in the development of multitarget-directed ligands (MTDLs) for simultaneous interaction with several pathological targets of AD. In this review, a selection of the most recent reports (2016-up to present) on metal chelators of MTDLs with multifunctionalities is presented. These compounds enable the hitting of several AD targets or pathways, such as modulation of specific biometal ions (e.g., Cu, Fe, Zn) and of protein misfolding (β-amyloid and tau protein), anti-oxidant activity and AChE inhibition. The properties found for these hybrids are discussed in comparison with the original reference compounds, some MTDLs being outlined as leading compounds for pursuing future studies in view of efficient potential applications in AD therapy.
Keywords: antioxidant properties